Teori Semiotik Pierce Pada Tarian O Uwi Desa Bomari Langa, Kecamatan Bajawa, Kabupaten Ngada - Marianus Woda Liru; Eugrasia Fridolin Paba; Eugenia Cindy Julia Pera; Andreas Arif Penalosa; Wilhelmina Senge; Agnesia Helentina Rabu; Hironimus Nuwa; Anita Ciline Djea; Desti Desti (Institut Nalanda, 2024)
This research uses a qualitative descriptive method where the data analyzed is in the form of pictures depicting the O Uwi dance movements, as well as words, phrases or sentences that represent the lyric of O Uwi dance. Data collection techniques in this research used interview, recording and documentation techniques. The data source of this research is a primary data source where the data was taken directly in Langa, Bomari Village, Bajawa District, Ngada Regency. The informan interviewed was the Langa traditional leader, Aloysius Bajo. The results of this research will be explained using Sanders Pierce's semiotic theory, namely icons, indices and symbols.